Engineers’ continuing professional development - Vieira, J. M. P. (2021)
The challenging environment of continuous technological evolution requires skilled and competent engineers who can contribute towards achieving the United Nations Sustainable Development Goals and who can strive for innovative and sustainable solutions. To be able to do so, engineers should continuously acquire new knowledge and skills, and update their existing skills to incorporate individual and team competencies. Continuing Professional Development (CPD) can play a fundamental role in adapting the engineer to technological innovations and new working methods to better fulfill his or her commitment to society. In this regard, engineering professional certification systems could be of paramount importance for the recognition of engineering qualifications and professional competencies worldwide by establishing minimum requirements of knowledge, skills and competencies for the engineering profession.